2018
DOI: 10.1007/s00384-018-2995-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical recurrence in Crohn’s disease: a comparison between different types of bowel resections

Abstract: Reoperation frequency in Crohn's disease is lower after ileocolic resection than after other types of bowel resections. Surgical recurrence in Crohn's disease tends to maintain the disease location of the primary operation. One third of Crohn's patients undergoing an end stoma operation will still need new bowel resections due to recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…The present ndings revealed a difference between endoscopic recurrence in the anastomotic site and the causative lesion related to the reoperation. Among other studies presented thus far, Aaltonen G et al reported that the majority of cases of surgical recurrence (71.4%) were because of a lesion located in the proximal portion of the site of anastomosis and required a new ileocolic resection [3], while other studies also concluded that surgical recurrence after an ileocolic resection is more common in the anastomotic site [4,5]. Furthermore, the reoperation rate after stoma construction is high in CD patients.…”
Section: Discussionmentioning
confidence: 97%
“…The present ndings revealed a difference between endoscopic recurrence in the anastomotic site and the causative lesion related to the reoperation. Among other studies presented thus far, Aaltonen G et al reported that the majority of cases of surgical recurrence (71.4%) were because of a lesion located in the proximal portion of the site of anastomosis and required a new ileocolic resection [3], while other studies also concluded that surgical recurrence after an ileocolic resection is more common in the anastomotic site [4,5]. Furthermore, the reoperation rate after stoma construction is high in CD patients.…”
Section: Discussionmentioning
confidence: 97%
“…reported that the majority of cases of surgical recurrence (71.4%) were because of a lesion located in the proximal portion of the site of anastomosis and required a new ileocolic resection [3], while other studies also concluded that surgical recurrence after an ileocolic resection is more common in the anastomotic site [4,5]. Furthermore, the reoperation rate after stoma construction is high in CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Aaltonen G et al reported that the majority of cases of surgical recurrence (71.4%) were because of a lesion located in the proximal portion of the anastomosis and required a new ileocolic resection [4], while other studies also concluded that surgical recurrence after an ileocolic resection is more common in the anastomosis [5,6]. Furthermore, the reoperation rate after stoma construction is high in CD patients.…”
Section: Discussionmentioning
confidence: 99%